NodeMCU-enabled intelligent fertigation system for efficient water and nutrient management - Zatun Najhah Kurasli, Engku Nor; Abdullah, Norzilawati; Wan Salleh, Wan Mohd Za’im Bin (Southeast Asian Journal of Technology and Science, 2024)
Fertigation is a methodology that encompasses the direct application of fertilizers via irrigation water systems, thereby augmenting the delivery of nutrients to plants and reducing the wastage of valuable nutrients, consequently enhancing both crop yield and quality. Specific injection tools are used to introduce nutrient solutions into the irrigation water (Shukla et al., 2018). This technique is particularly beneficial for farmers managing a large quantity of plants, as it streamlines the process by ensuring a consistent supply of water and fertilizers to the crops. Most farmers cannot be present in their fields around the clock and this method demands continuous monitoring of fertilizer and water levels. As a result, this project aims to showcase how the Smart Fertigation system project will address the challenges faced by farmers who adopt this method. This project promotes a monitoring mechanism that tracks water and fertilizer levels and monitors moisture and ambient temperature around the plants, thereby providing farmers with comprehensive insights.